Producción de frutos de Gleditsia amorphoides (Fabaceae) y abundancia de Bruchidius endotubercularis Arora (Coleoptera: Chrysomelidae) en Formosa, Argentina - Godoy, Marcela (2018)
Gleditsia amorphoides (Griseb.) Taub. is a tree species native to South America. It is known for its good quality wood and for its fruits that contain a rubber for industrial uses. One of the causes for the reduction of the production of viable seeds in forest trees is the damage caused by predators of fruits and seeds. The relationship between fruit production and predators is not known for G. amorphoides. Therefore, in this study, we evaluated the fruit production in this three species and the abundance of specimens of the Subfamily Bruchinae associated to G. amorphoides. The study was carried out in three localities of the Formosa Province in the Northeast of Argentina for three consecutive years. We found a single species of Bruchinae, identified as Bruchidius endotubercularis Arora. The results showed the existence of variability in the production of G. amorphoides fruits between years, but not between locations. The abundance of insects remained constant, not responding to the variation in the production of fruits between years. In this study, we report for the first time, the occurrence of B. endotubercularis associated with G. amorphoides in Argentina.